Finland's exchange rate regime and European integration - Markku Kotilainen; Tapio Peura (Bank of Finland, 1988)
Finland's participation in the deepening European integration means a considerable change in her economic policy setting. Liberalization of capital movements and financial services will increase interest and exchange rate sensitivity. To maintain stability, tighter coordination of economic policies is required. The integration of Finland's foreign trade and the markets of the factors of production with the EC will cause pressures to adjust Finland's exchange rate regime to the changing conditions. Of the available alternatives participation in the European Monetary System (EMS) would seem to be excluded for political reasons. In practice, the alternatives to be considered are the pegging of the markka to the ECU basket of the EC countries, or the increase of the weight of the EC countries' currencies in the present basket. At the moment there is no need for changing the weights. The need for change would, however, increase if other EFTA countries joined the EMS or pegged their currencies to the ECU, or if the importance of the US dollar for the Finnish economy substantially decreased.
URN:NBN:fi:bof-201908051339
Keywords: 330